EFFECTIVENESS OF USINGFODDER CONCENTRATED PRODUCT «ZHIVINA» IN GROWING CHICKENS-BROILERS - Блюсюк, С. М.; Бучковська, В. І.; Євстафієва, Ю. М.; Харкавлюк, В. І. (Podilian Bulletin: Agriculture, Engineering, Economics, 2016)
For solving actual questions of reformation of poultry breeding branch it is necessary to have a systemic approach with clear understanding of branch structure as a system which sections interact between themselves in coordination. In the article there are the results of research on studying of effectiveness of using fodder concentrated product «Zhivina» while growing chickens-broilers cross Ross- 308. According to the methods for carrying out the experiment there were selected 40 heads of daily chickens which, by the principle of analogy, were formed into two groups of 20 heads (10 cocks and 10 hens) in each one. The experiment has lasted for 42 days. During the period of growing of chickensbroilers the difference in feeding poultry of controlled and experimental groups consisted in substitution of 12% sunflower oilcake for fodder concentrated product «Zhivina». The results of experiments showed the effectiveness of feeding with fodder concentrated product. The including of fodder concentrated product «Zhivina» into the composition of the main mixed fodder has led to change of productivity of chickens-broilers under the influence of different components of mixed fodder. In such way the consumption of fodder by young poultry which got the main mixed fodder duringthe experiment was 2,06 kg on 1 kg of growth of living bulk, while the chickens-broilers which were fed by fodder concentrated product «Zhivina» consumed the main fodder on 3,4% economically. For feeding of chickens-broilers during the whole period of their growing it is recommended to use the fodder concentrated product «Zhivina» as a component of mixed fodder substituting 12% sunflower oilcake by it.